If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + 12 = 18 Reorder the terms: 12 + 4q = 18 Solving 12 + 4q = 18 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4q = 18 + -12 Combine like terms: 12 + -12 = 0 0 + 4q = 18 + -12 4q = 18 + -12 Combine like terms: 18 + -12 = 6 4q = 6 Divide each side by '4'. q = 1.5 Simplifying q = 1.5
| 4-8x=3(1-2x)-5x | | (6x+8)(8x-6)= | | 4=5x-31 | | 4x-5=13x-15 | | -1/2(x-4)-1/5(x-5)=x+9 | | n+(n+1)=111 | | g(x)=-3x^2+0.06x+4 | | (x-4)/(x-3)-(x-1)/(3-x) | | x/4+17=9 | | (5)/(t-1)+3/t | | 23.4-x=0 | | 2x+5-9=3x-15 | | -3=18-x | | 2n+5=4(n+2)-a | | p-6p=-4 | | 4y-9=13 | | 2y+6x=-14 | | n+17=35 | | n+25=30 | | x^3+14x^2+52x+21=0 | | -26+5x=-1 | | 58-2x=16x+16 | | 15000+7x=1210+9x | | 1/6(6x-3)=6(2+x)-5x | | x-6=0.666(x-3) | | 3x^2-6x+4= | | -1.25+2.3x=1.51 | | V=800(5/20) | | 8-3x=-4 | | 6+12=-79-7x | | 15x^4y^2/5x^3y^2 | | -4(-3p+7)=-100 |